DEVELOPMENT OF E-GANER (ELECTRONIC GEOGRAPHY CORNER) ON DISASTER MITIGATION AND ADAPTATION MATERIALS - Maghfiroh, Ainun; Wahyudi, Adip; Mutia, Tuti; Putra, Alfyananda Kurnia (Universitas Muhammadiyah Mataram, 2024)
Abstract: In modern education, digital technology is utilized to enhance learning activities and promote the development of the 4C skills: critical thinking and problem-solving, creativity, and innovation, communication, and collaboration. This research aims to develop and evaluate the feasibility of e-Ganer instructional materials, which concentrate on disaster mitigation and adaptation topics. The research methodology utilized in this study is research and development (R&D), following the A.D.D.I.E. model. Data collection is performed through non-test methods, specifically employing needs analysis and teaching material feasibility questionnaires. Data analysis is conducted using quantitative descriptive techniques. The e-Ganer product assessment yielded an average score of 94% from the material expert and 87.4% from the teaching material media expert. The product trial with teachers scored 83.3%, while the trial with students scored 85%. As a result, the e-Ganer teaching material is categorized as highly feasible and can be utilized in the educational process to support the achievement of learning objectives. Suggestions for further research include improving digital teaching materials in other subjects based on the need for teaching material development and evaluating the effect of using digital teaching materials on student learning outcomes to support the achievement of learning objectives.Abstrak: Pada pendidikan kontemporer, teknologi digital dimanfaatkan untuk mendukung kegiatan pembelajaran dan mendorong pengembangan keterampilan 4C (berpikir kritis dan pemecahan masalah, kreativitas dan inovasi, komunikasi, dan kolaborasi). Penelitian ini bertujuan untuk mengembangkan dan mengkaji kelayakan bahan ajar e-Ganer yang difokuskan pada materi mitigasi dan adaptasi bencana. Metodologi penelitian yang dimanfaatkan ialah penelitian dan pengembangan (R&D) dengan menggunakan model A.D.D.I.E. Pengumpulan data dikerjakan melalui metode non-tes, dengan menggunakan analisis kebutuhan dan kuesioner kelayakan bahan ajar. Analisis data dikerjakan dengan menggunakan teknik deskriptif kuantitatif. Rata-rata hasil penilaian produk e-Ganer oleh ahli materi memperoleh skor 94%, oleh ahli media bahan ajar memperoleh skor 87,4%, uji coba produk kepada guru memperoleh skor 83,3%, dan uji coba produk kepada siswa memperoleh skor 85% sehingga bahan ajar e-Ganer termasuk dalam kategori sangat layak dan dapat dimanfaatkan dalam proses pendidikan untuk membantu mencapai tujuan pembelajaran. Saran untuk penelitian selanjutnya adalah penyempurnaan bahan ajar digital untuk mata pelajaran lain berdasarkan kebutuhan pengembangan bahan ajar serta evaluasi pengaruh penggunaan bahan ajar digital terhadap hasil belajar siswa untuk mendukung ketercapaian tujuan pembelajaran.